THE FIRST YEAR OF APPRENTICESHIP: FROM EXPECTATIONS TO REALITY - FRIEDMANN, Zdeněk (Trends in education, 2010)
The paper presents results of a questionnaire investigation conducted among students/appprentices in the first year of secondary vocational schools. The aim of the investigation was to identify the principal motives and circumstances of their choice of the studied field (craft), to find out the degree of their satisfaction with the choice and note the differences between expectations and school reality from their point of view. Special attention is paid to apprentices with special educational needs.
Keywords: Career choice; satisfaction with the choice; secondary vocational school; apprentices; crafts; pupils with special educational needs.